A Logic for a Critical Attitude? - Boem, Federico; Bonzio, Stefano (Logic and Logical Philosophy, 2022)
Individuating the logic of scientific discovery appears a hopeless enterprise. Less hopeless is trying to figure out a logical way to model the epistemic attitude distinguishing the practice of scientists. In this paper, we claim that classical logic cannot play such a descriptive role. We propose, instead, one of the three-valued logics in the Kleene family that is often classified as the less attractive one, namely Hallden’s logic. By providing it with an appropriate epistemic interpretation, we can informally model the scientific attitude.